Financial Metrics Impact on LQ-45 Stock Price Changes: Evidence from IDX: Dampak Metrik Keuangan pada Perubahan Harga Saham LQ-45: Bukti dari IDX - Satriaji, Muhammad Bhakti Dede; Maryanti, Eny (Indonesian Journal of Law and Economics Review, 2023)
This quantitative research investigates the influence of Return On Assets (ROA), Net Profit Margin (NPM), Earnings Per Share (EPS), and Debt to Equity Ratio (DER) on stock price fluctuations within the LQ-45 index companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2019. Employing SPSS tests, including multicollinearity and heteroscedasticity assessments, this study reveals that ROA, NPM, EPS, and DER collectively exert a significant impact on stock price changes. These findings underscore the relevance of financial performance metrics in gauging stock price dynamics, offering valuable insights for investors and market analysts. Highlights: Financial Metrics Significance: This research emphasizes the crucial role of financial metrics in understanding stock price fluctuations. LQ-45 Companies Impact: It assesses the impact of financial metrics on stock prices within the specific context of LQ-45 companies. Empirical Evidence: The study presents empirical evidence from the Indonesia Stock Exchange, enhancing its practical relevance for investors and analysts. Keywords: Financial metrics, stock price changes, LQ-45 companies, Indonesia Stock Exchange, SPSS analysis.